Examining deep and shallow Adriatic bora events - Kuzmić, Milivoj; Grisogono, Branko; Li, Xiaoming; Lehner, Susanne (Quarterly Journal of the Royal Meteorological Society, 2015)
This note examines two Adriatic bora events recorded in TerraSAR-X (TS-X) images taken in the winters of 2011 (Case 1) and 2012 (Case 2). In Case 1, the TS-X captured an image of a deep anticyclonic bora, whereas in Case 2 a shallow cyclonic bora was sampled. High-resolution TS-X images resolved the finer bora spatial structure to a scale of ≈1 km, which has not previously been reported in bora research. In particular, the structures in Case 2 appear to be driven by surface convective heat fluxes caused by substantial temperature differences between the relatively high sea surface temperature (SST) and the overflowing very cold air. The Weather Research and Forecasting (WRF) model simulations used to aid the analyses suggest that the very low upwind 2m temperature in Case 2 reinforced the orographic wave breaking by enhancing the cross-mountain pressure gradient. The ensuing strong cross-mountain flow was responsible for the appearance of secondary jets in the lee of Mount Velebit, for which the TS-X Case 2 scene provides the first satellite-borne evidence.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Adriatic Sea; Bora wind; TerraSAR-X; WRF model